PENGARUH KOMPETENSI DAN INDEPENDENSI AUDITOR TERHADAP KUALITAS AUDIT (Survei Terhadap Auditor Yang Bekerja Pada Kantor Akuntan Publik Di Kota Palembang) - Pradana, Aditya; Muklis, Muklis; Dewi Yanti, Nurjana (LPPM Universitasdiwangsa Jambi, 2018)
The title of this research is the influence of auditor’s competence and independence toward audit quality. The aim of this research is to analyze theinfluence of competence and independence toward audit quality simultaneouslyand partially. Kind of this research is descriptive that is survey in publicaccountant office in Palembang, which have recorded in IAPI 2010. In collectingthe date the researcher uses library study and field study. Time period which isused is cross sectional. Public accountant office which is researched is 7 (seven)public accountant office with 61 auditor’s as respondent. Data analysis toexamine the hypothesis uses multiple regression with the help of program SPSSV.12. Independent variable in this research is competence and independence,while dependent variable is audit quality. The result of this research show’s thatauditor’s competence and independence simultaneously influences the auditquality significantly. The auditor’s competence and independence partiallyinfluences the audit quality significantly.